Reimagining the Home. (1st March 2021) - Allen, Isabel
Abstract: Isabel Allen is Editorial Director of BEAM (Built Environment and Architecture Media). Here she describes how three decades of innovation – and an ongoing delight in the poetic possibilities of the home – make AHMM perfectly positioned to deliver a new kind of housing that responds to the practical and psychological challenges of these extraordinary times.